Implementasi manajemen risiko keuangan pada UMKM Batik selama pandemi Covid-19 - Rudi Santoso; Martinus Sony Erstiawan (Universitas Pendidikan Indonesia (UPI), 2023)
COVID-19 has had an impact on the Indonesian economy. MSMEs are one of the parties experiencing systematic risk caused by Covid-19. Some MSMEs went bankrupt, and others were able to survive. MSMEs that can survive must continue to struggle during difficulties. One of the efforts to avoid this systematic risk is to apply risk management. This Community Service activity aims to provide knowledge, insight, and skills, especially batik UMKM players in Sekoto, Badas District, Kediri Regency. The knowledge provided is about business risk management. Risk management is closely related to financial management. The results of the activity indicated an increase in the literacy of batik MSMEs in terms of implementing financial risk in facing future systematic risks.